Find the difference.
(4x 2 - 6x + 8) - (3x 2 - 6x + 2)
x2 + 6
7x2 - 12x - 6
x2 + 12x + 6
x2 - 12x - 6

(4x^2 - 6x + 8) - (3x^2 - 6x + 2) = 4x^2 - 6x + 8 - 3x^2 + 6x - 2 = x^2 + 6

Question

Asked 2/28/2014 10:08:24 AM

Updated 9/15/2014 8:33:39 AM

1 Answer/Comment

Rating

3

(4x^2 - 6x + 8) - (3x^2 - 6x + 2)

= 4x^2 - 6x + 8 - 3x^2 + 6x - 2

= x^2 + 6

= 4x^2 - 6x + 8 - 3x^2 + 6x - 2

= x^2 + 6

Added 9/15/2014 8:33:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/15/2014 8:37:34 AM]

(12x 2 - 10x -12) ÷ (3x + 2)
2x - 3
4x + 6
3x + 2
4x - 6 **Weegy:** When you multiply and simplify (x + 4)(x^2 - 3x + 2) you get the result of x^3 + x^2 - 10x + 8. **User:** Solve for x.
|2x - 8| > 6
x > 7 or x 1
x > -1 or x -7 (More)

Question

Not Answered

Updated 2/25/2014 12:05:40 AM

2 Answers/Comments

Simplify the expression 4x^2+10x-6/2x-1

Question

Not Answered

Updated 2/28/2014 11:20:28 AM

1 Answer/Comment

(12x 2 - 10x -12) ÷ (3x + 2) **Weegy:** When you multiply and simplify (x + 4)(x^2 - 3x + 2) you get the result of x^3 + x^2 - 10x + 8. **User:** Two runners start 30 kilometers apart and run toward each other. They meet after 3 hours. One runner runs 2 kilometers per hour faster than the other runner. What rate do they run?
2 km/hr and 4 km/hr
3 km/hr and 5 km/hr
5 km/hr and 7 km/hr
4 km/hr and 6 km/hr **Weegy:** 4 km/hr and 6 km/hr. **User:** Solve for x.
2(x - 4) = 6(x + 2)
-2
-1
-5
4 **Weegy:** The answer is 5. **User:** Completely factor the polynomial.
100x 2 - 25
25(2x + 1)(2x - 1)
(10x + 5)(10x - 5)
(20x + 5)(5x - 5)
25(4x2 - 1) (More)

Question

Not Answered

Updated 8/30/2014 5:49:19 PM

3 Answers/Comments

2(x - 4) = 6(x + 2)

2x - 8 = 6x + 12

-4x = 20

x = -5

2x - 8 = 6x + 12

-4x = 20

x = -5

Added 2/28/2014 11:10:27 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [2/28/2014 1:30:17 PM]

100x^2 - 25 = 25(2x + 1)(2x - 1)

Added 2/28/2014 11:11:29 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [2/28/2014 1:30:18 PM]

(12x^2 - 10x -12) ÷ (3x + 2)

= (12x^2/3x+2) - (10x/3x+2) - (12/3x+2)

= 4x - 6

= (12x^2/3x+2) - (10x/3x+2) - (12/3x+2)

= 4x - 6

Added 8/30/2014 5:49:19 PM

This answer has been confirmed as correct and helpful.

solve x x/4+6=10 **Weegy:** x + 6 = 6 x = 6 - 6 x = 0 **User:** Simplify.
8 - 3(4 - 2x)
20 - 10x
-4 - 6x
6x - 4
8 - 6x **User:** solve x/4+6=10 **Weegy:** x = y + 4 (More)

Question

Expert Answered

Updated 2/28/2014 11:03:13 AM

1 Answer/Comment

x/4+6=10

x/4 = 10 - 6 = 4

x = 16

x/4 = 10 - 6 = 4

x = 16

Added 2/28/2014 11:03:13 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [2/28/2014 1:33:27 PM]

Solve the system of equations.
4x - 4y = 10
3x + 2y = 5

Question

Not Answered

Updated 8/27/2014 7:15:21 PM

1 Answer/Comment

4x - 4y = 10 divided by 2 on both sides the result is:

2x - 2y = 5 (equ. 1)

3x + 2y = 5 (equ. 2)

adding up equations 1 and 2 the result is:

5x = 10

x = 10/5 = 2

4(2) - 4y = 10

-4y = 10 - 8 = 2

y = 2/-4 = -1/2

The solution for the system 4x - 4y = 10 3x + 2y = 5 is (2, -1/2)

2x - 2y = 5 (equ. 1)

3x + 2y = 5 (equ. 2)

adding up equations 1 and 2 the result is:

5x = 10

x = 10/5 = 2

4(2) - 4y = 10

-4y = 10 - 8 = 2

y = 2/-4 = -1/2

The solution for the system 4x - 4y = 10 3x + 2y = 5 is (2, -1/2)

Added 8/27/2014 7:15:21 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/27/2014 7:26:53 PM]

27,687,955

questions answered

There are no comments.